Report of the chairman... - Afiff, Saleh ([s.n.] [S.l.], 1994)
Summarizes the principal observations and views expressed by government representatives on issues related to debt and development. Provides a summary of the key measures that should be taken by creditor and debtor countries, multilateral financial institutions, and the international community at large, to resolve effectively the continuing debt problem of debt distressed developing countries. Presents recommendations on possible areas for South South cooperation.